Development of Agranulocytosis after Discontinuation of Methimazole: An Unusual Case - Rıfkı Üçler; Murat Atmaca; Ömer Candar; Murat Alay; Burhan Göy; Erdal Kara; Mahfuz Turan; Yusuf Demir (Case Reports in Endocrinology)
Agranulocytosis is a rare and critical adverse effect of antithyroid drugs (ATD). The occurrence of agranulocytosis in continuous ATD treatment patients is well known; however, a case of ATD agranulocytosis occurring following the discontinuation of methimazole (MMI) treatment is not a usual situation. We herein describe a case of a 41-year-old woman who was previously administered methimazole (MMI) for ten days and developed ATD-induced agranulocytosis and symptoms of an upper respiratory tract infection after three weeks following discontinuation of MMI treatment. A thorough hematologic and serological evaluation did not disclose an alternative cause for the agranulocytosis. After receiving empirical antibiotic treatment, she responded successfully with clinical improvement of her symptoms and resolved neutropenia on the seventh day. This case is atypical because agranulocytosis developed after discontinuation of MMI, which strengthens the importance of remaining alert for signs of agranulocytosis even after discontinuation of ATD treatment.